Quantification of GHB by SPE and GC-MS-MS in whole blood samples for forensic purposes - Castro, André Lobo (2013)
Introduction: Gamma-Hydroxybutyrate (sodium hydroxybutyrate; sodium oxybutyrate; GHB) is known to be an endogenous, naturally occurring, short-chained fatty acid found in mammalian tissues, with wide distribution and action in several brain areas (hipothalamus, basal ganglia). Although it was first synthesised in 1960, it soon was noticed that it is no more than an endogenous compound. With more than 30 years of clinical use, both in Europe and the U.S.A, its illicit use includes recreational use, muscle building effects in bodybuilders and drug-facilitated sexual abuse. Used as a club drug, alone or mixed with other substances, it´s symptoms mimetize MDMA, ketamine and ehtanol. On the ohter hand, it is also used for drug-facilitated sexual abuse (DFSA) purposes. Aim: In this work, the authors developed and validated an analytical procedure for GHB detection in whole blood (in vivo and post-mortem), for forensic purposes. Material and Methods: The analytical method was developed preparing the samples by a SPE procedure with MCX OASIS® cartridges, followed by derivatization with BSTFA-TMCS (99:1) and instrumental analysis developed by GC-MS-MS in a Triple Quadrupole apparatus (BRUKER). Results and Discussion: The described method shows good fitness for purpose for whole blood samples. The obtained LOD and LOQ were 200 ng/mL, for 100 uL of sample. This increase in sensitivity was obtained due to an optimized SPE procedure and an instrumental technique state-of-the-art. The work range started at 200 ng/mL, far below the suggested cut-off for whole blood samples (5-10 mg/L). These results will allow the possibility to distinguish post-mortem production, endogenous values and external consumption, whenever this diagnosis should be determined, being applicable to forensic purposes.